On the Complexity of Correlating a Graduate Program’s Experiences with the Success of its Graduates: a Response to Dixon et al. (2015) - Carr, James E. (Behav Anal Pract, 2015)
Dixon et al. Behavior Analysis in Practice 8:7–15, 2015 evaluated the scholarly productivity of instructors in graduate-level, behavior-analytic training environments as a potential quality metric related to practitioner training. In our reply, we discuss the authors’ premise and methodology, suggest alternative conceptualizations, and recommend a more comprehensive and germane approach to the task.